High capacity and cycle stability Rechargeable Lithium–Sulfur batteries by sandwiched gel polymer electrolyte. (20th August 2016) - Yang, Wu; Yang, Wang; Feng, Jiani; Ma, Zhipeng; Shao, Guangjie
Abstract: A novel sandwiched gel polymer electrolyte (GPE) was prepared using a facile method as separator solely for rechargeable Lithium–Sulfur batteries. As a result of the strong physical shielding and chemical absorption of GPE, the separator can not only suppress shuttle effect in ether-based electrolyte, but also improve utilization of sulfur significantly resulting in a high capacity. The PVDF layers could absorb ether-based electrolyte largely and then enhance Li + transfer; the PMMA layer can be utilized to trap the dissolved polysulfides. Lithium–Sulfur batteries with the sandwiched GPE separator shows an encouraging electrochemical performance. A high initial discharge capacity of 1711.8 mAh g −1 is obtained, and the capacity retains at 1145.3 mAh g −1 after 50 cycles at 200 mA g −1, which is higher than that of the cell with the commercial separator. These results indicate that the appropriate GPE separator is more suitable in Lithium−Sulfur batteries applications.